Consumer perceptions of conventional and alternative protein sources: a mixed-methods approach with meal and product framing - Possidónio, C.; Prada, M.; Graça, J.; Piazza, J. (Appetite, 2021)
Understanding consumer perceptions of meat alternatives is key to facilitating a shift toward more sustainable food consumption. Importantly, these perceptions may vary according to the characteristics of the consumer (e.g., preferences, motivations), the product (e.g., sensory attributes) and the encounter (e.g., how the meat alternative is presented/framed). Qualitative and quantitative methods were applied to examine consumer perceptions of five proposed alternatives to meat: legumes, tofu, seitan, lab-grown meat, and insects. In Study 1, 138 participants provided free associations with regards to conventional animal proteins (e.g., red/white meat, fish) and the five alternatives. Three profiles of consumers were identified: (1) hedonically motivated meat eaters uninterested in meat substitutes; (2) health-oriented meat eaters open to some meat substitutes; and (3) ethically conscious meat avoiders positively oriented to most meat alternatives. In Study 2, the presentation of the product was experimentally manipulated: 285 participants evaluated the same five meat alternatives along several dimensions (e.g., edibility, healthiness), either when framed as an individual product or as part of a larger meal. Overall, most meat alternatives benefited from a meal framing, with the notable exception of legumes, which benefited from an individual framing, and insects which were evaluated quite negatively regardless of framing. The present findings suggest that there is not a single way to frame all meat alternatives that will improve their appeal to all consumers.